Abortion: Humanized Attention and Legal Aspects (Brazilian Journal of Health Research, 2019)
Introduction: Abortion is defined as termination of pregnancy until the 20th / 22nd week and with the fetus weighing less that 500g.. Objective: Theoretical study aimed at analyzing abortion and its licit and illicit practices based on the Fundamental Principle of Human Dignity and on its constitutional perspective, by taking into account its ethical, penal, normative and deontological considerations. The deontological consideration was based on the professional codification of medicine in Brazil. Methods: Problem contextualization was based on the presentation of data collected from previous statistical studies. We worked with the theoretical analysis about the negative impacts of criminalizing abortion made in Brazil due to socioeconomic issues. Results: Religious aspects and fundamental freedom were listed among arguments addressed in the text; argument biases were pro and against abortion. These biases included conscientious objection and its possible limits. Conclusion: Ratification of due respect for human dignity is achieved by reinforcing the maintenance of respect for the right to health regardless of the nature of the act, such as being in compliance, or not, with current provisions of Brazilian law.